2023
DOI: 10.1021/acs.nanolett.3c01751
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Phase Transition in Ultrathin Ga2O3 Nanowires

Jiaheng Wang,
Xiaoxi Guan,
He Zheng
et al.

Abstract: Gallium oxide (Ga 2 O 3 ) has attracted extensive attention as a potential candidate for low-dimensional metal-oxide-semiconductor field-effect transistors (MOSFETs) due to its wide bandgap, controllable doping, and low cost. The structural stability of nanoscale Ga 2 O 3 is the key parameter for designing and constructing a MOSFET, which however remains unexplored. Using in situ transmission electron microscopy, we reveal the size-dependent phase transition of sub-2 nm Ga 2 O 3 nanowires. Based on theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The stabilization of the β-Ga 2 O 3 phase for a size smaller than 4.2 nm confirms the results reported by Fang et al 58 and it could be explained considering that the kinetic barriers that need to be overcome to stabilize different polymorphs can be strongly altered by stress and strain, promoting or hindering the stabilization of metastable polymorphs. The same effect of size dependence stabilization of the γ- and β-phase was also recently demonstrated for ultrathin Ga 2 O 3 nanowires by Wang et al , 59 suggesting that positive or negative strains could inhibit the phase transition to the γ-phase at very small sizes. For sizes larger than about 22 nm, the β-Ga 2 O 3 polymorph is again the more thermodynamically favored.…”
Section: Resultssupporting
confidence: 74%
“…The stabilization of the β-Ga 2 O 3 phase for a size smaller than 4.2 nm confirms the results reported by Fang et al 58 and it could be explained considering that the kinetic barriers that need to be overcome to stabilize different polymorphs can be strongly altered by stress and strain, promoting or hindering the stabilization of metastable polymorphs. The same effect of size dependence stabilization of the γ- and β-phase was also recently demonstrated for ultrathin Ga 2 O 3 nanowires by Wang et al , 59 suggesting that positive or negative strains could inhibit the phase transition to the γ-phase at very small sizes. For sizes larger than about 22 nm, the β-Ga 2 O 3 polymorph is again the more thermodynamically favored.…”
Section: Resultssupporting
confidence: 74%
“…Consequently, there could be potential discrepancies between the in situ and ex situ observations. In this sense, J. Wang et al 39 showed experimentally and by first-principles calculations that similar transitions occur in Ga 2 O 3 nanowires. From their results, the calculated surface energy of {600}β is smaller than that of {400}γ.…”
Section: Resultsmentioning
confidence: 90%
“…Consequently, there could be potential discrepancies between the in situ and ex situ observations. In this sense, J. Wang et al 39 showed experimentally and by first-principles calculations that similar transitions occur in Ga 2 O 3 nanowires. From their results, the calculated surface energy of {600}b is smaller than that of {400}g. Considering that a TEM-lamella has a higher surface area/volume ratio than a bulk sample, the observed transition in this work could be influenced by the reduction of the surface energy.…”
Section: Discussionmentioning
confidence: 90%
“…Over the past few years, field-effect transistors (FET) have experienced expansion, and an increasing number of authors are conducting research on their reliability. There has been significant research conducted both domestically and internationally on electrospinning technology and its applications in the field of FETs based on metal oxide nanowires [7][8][9][10]. Modern materials are used for both NMOS and PMOS transistors, and nanowire MOSFETs are being developed for various applications, which has spurred the realization of numerous experiments and the characterization of these components.…”
Section: Introductionmentioning
confidence: 99%